Advancing the Promise of Digital Technology and Social Media to Promote Population Health. (December 2019) - Allegrante, John P.; Auld, M. Elaine
In June of 2018, the Society for Public Health Education partnered with The George Washington University Milken Institute School of Public Health, University of Maryland School of Public Health at College Park, and the Public Good Projects to convene the inaugural Digital Health Promotion Executive Leadership Summit in Washington, D.C. We launched the 2018 Summit for several reasons. First, because of the ubiquity of digital technology and reach of social media, it had become apparent to us that the time was right to bring greater focus to the promise that digital technology and social media hold for improving the public's health. Second, while other forums were discussing uses of mHealth and eHealth, it was clear the public and private sectors were talking within siloes; thus we believed that more needed to be done to catalyze a dialogue among the academic, industry, and government sectors to share their efforts and to examine the opportunities—and challenges—of forging collaborative partnerships in developing and evaluating the next generation of digital information and health communication technologies. And third, we hoped to facilitate a conversation among leaders from each of these sectors that would result in a consensus on a "Common Agenda" for future actions to advance digital health promotion efforts.